Gender differences and managerial earnings forecast bias: Are female executives less overconfident than male executives? - Ravi Lonkani (2019)
© 2018 Elsevier B.V. This study examines whether firms with female executives forecast company earnings more conservatively. Consistent with the selectivity hypothesis, the results reveal firms with female CEOs tend to make conservative earnings forecasts in a perceived positive situation and firms with a higher percentage of female directors on the board are more likely to forecast earnings conservatively in a perceived negative situation. The conservativeness of female executives is not caused by lower management ability. This conservative behavior is not caused by personal factors such as military status, level of education, or area of study.